(untitled) (Acta Polytechnica CTU Proceedings, 2015)
We have developed a new model of the Doppler tomography using total variation minimization (DTTVM). We demonstrated that this method can reconstruct localized and non-axisymmetric profiles possibly having sharp edges in the Doppler map. We apply this model to the real data of the dwarf nova, WZ Sge in superoutburst. DTTVM can reproduce the observed spectra with a high precision, while the previous models fail to reproduce localized sources.